The analysis of operation of plasma-filled helical TWT taking into account spatial harmonics - Antipov, V.S.; Bez’yazychny, I.A.; Berezhnaya, I.V.; Borodkin, A.V.; Galaydych, K.V.; Kornilov, E.A.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2008)
Theoretical and the experimental results of studies of electrodynamics characteristics of the TWT on the basis of helical slow-wave structure (SWS) are presented. Представлені теоретичні та експериментальні результати дослідження електродинамічних характеристик ЛБХ на основі плазмонаповненої спіральної уповільнюючої структури. Представлены теоретические и экспериментальные результаты исследования электродинамических характеристик ЛБВ на базе плазмонаполненной спиральной замедляющей структуры.